2021
DOI: 10.1021/acs.jafc.0c07018
|View full text |Cite
|
Sign up to set email alerts
|

Circ11103 Interacts with miR-128/PPARGC1A to Regulate Milk Fat Metabolism in Dairy Cows

Abstract: The quality of milk is inseparable from its milk components, and fatty acid content is a key factor affecting the quality of milk. In this study, the miRNA and mRNA profiles of the bovine mammary gland tissue during the dry period and the peak lactation period were determined through high-throughput sequencing. In total, 72 miRNA−mRNA regulatory pathways were screened, including miR-128/PPARGC1A regulatory pathways. miR-128 can directly target PPARGC1A and inhibit its expression. In addition, the study also ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 41 publications
1
30
0
Order By: Relevance
“…Fatty acids (FAs) can be divided into four types according to the length of the carbon chain, namely short-chain fatty acids (containing 2-4 carbon atoms, SCFAs), medium-chain fatty acids (containing 6-12 carbon atoms, MCFAs), long-chain fatty acids (containing 13-18 carbon atoms, LCFAs) and very long-chain fatty acids (containing 20 or more carbon atoms, VLCFAs) [1]. In this review, we will refer to VLCFAs, including C20:0, C20:1, C22:0, and others.…”
Section: Introductionmentioning
confidence: 99%
“…Fatty acids (FAs) can be divided into four types according to the length of the carbon chain, namely short-chain fatty acids (containing 2-4 carbon atoms, SCFAs), medium-chain fatty acids (containing 6-12 carbon atoms, MCFAs), long-chain fatty acids (containing 13-18 carbon atoms, LCFAs) and very long-chain fatty acids (containing 20 or more carbon atoms, VLCFAs) [1]. In this review, we will refer to VLCFAs, including C20:0, C20:1, C22:0, and others.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to livestock and poultry, some circRNAs have also been identified by high throughput sequencing and confirmed to participate in regulating their important biological process, such as embryos development ( Veno et al, 2015 ), formation of skeletal muscle fiber ( Li et al, 2020b ), hepatic lipid metabolism ( Huang et al, 2018 ), and adipogenic differentiation ( Li A. et al, 2018 ) in pig; muscle growth and development ( Wei et al, 2017 ; Li et al, 2018b ; Li et al, 2018c ; Liu et al, 2020 ; Shen et al, 2020 ; Yue et al, 2020 ; Elnour et al, 2021 ), testis development ( Gao et al, 2018 ), adipogenesis ( Jiang et al, 2020 ) and milk fat content ( Chen et al, 2021 ) in cattle; fat deposition in buffalo and yak ( Huang et al, 2019 ; Wang H. et al, 2020 ); intramuscular fat (IMF) content denoting a crucial indicator of meat quality in donkey ( Li et al, 2020a ); follicular development ( Shen et al, 2019 ), Marek’s tumourigenesis ( Wang L. et al, 2020 ) as well as muscle growth development ( Ouyang et al, 2018a ; Ouyang et al, 2018b ) in chicken. And it has yet indicated some functional circRNAs related to lipid metabolism, for instance, circFUT10 could promote bovine preadipocyte proliferation but inhibit adipocyte differentiation ( Jiang et al, 2020 ); circRNA_26852 and circRNA_11897, might get involved in porcine adipocyte differentiation and lipid metabolism ( Li A. et al, 2018 ); circ11103 could increase the triglyceride levels in bovine mammary epithelial cells and the contents of unsaturated fatty acids ( Chen et al, 2021 ); additionally, 19:45387150|45389986 and 21:6969877|69753491, were deemed as potential modulators of buffalo back subcutaneous adipose deposition ( Huang et al, 2019 ). These evidences intensively reveal an indispensable role of circRNA in lipid metabolism in livestock.…”
Section: Introductionmentioning
confidence: 99%
“…The circ_140 inhibited casein secretion and lipid formation in goat mammary epithelial cells ( 24 ). The circ_11103 increased the contents of triglycerides and unsaturated fatty acids in bovine mammary epithelial cells ( 25 ). In this study, we first confirmed the authenticity of circ_015343 by using RT-PCR and Sanger sequencing.…”
Section: Discussionmentioning
confidence: 99%